Regional Security in Southeast Asia : Beyond the ASEAN Way - Anthony, Mely Caballero (Book collections on Project MUSE., 2005)
The book examines ASEAN's mechanisms in managing challenges and threats to regional security. Its extensive analyses of the ASEAN story of managing regional security cover the different phases of ASEAN's development as a regional organization and explore the perceptible changes that have occurred in regional mechanisms of conflict management. The book also examines the roles of relevant actors beyond the states of ASEAN and the key interactions that have evolved over time, which have been instrumental in moving regional mechanisms beyond the ASEAN way. The book argues that the ASEAN way has not been impervious to change. As the association finds its way through periods of crises and continues to confront the many challenges ahead, ASEAN and its mechanisms are already being transformed beyond the narrow confines of the modalities associated with the ASEAN way. The changes in the political and security landscape of the region, as well as the democratic transitions taking place in some member states, have set the stage for a much more dynamic set of regional actors and processes that bring into question the kind of regionalism that is now taking place in the region. This book therefore attempts to capture these evolving dynamics and examines the way regionalism is changing in Southeast Asia.